The Induction and One-Step Purification of Acetylcholinesterase (AChE) from the Brain of Hybrid catfish after Exposed to Glyphosate - Thanomsit, Chutima; Nanthanawat, Phochit; Nanuam, Jakkaphun; Wattanakornsiri, Amnuay; Prasatkaew, Witchuda; Insuwan, Wilaiporn (Naresuan University Journal: Science and Technology (NUJST); Vol 29 No 1 (2021): January - March 2021, 2020)
Acetylcholinesterase (AChE) is classified as a specific biomarker for herbicide exposure in aquatic organisms. In this study, we investigated an AChE induction in the brain of juvenile and adult hybrid catfish after exposoure to glyphosate in sub-lethal concentration for quantifying the highest yield of AChE. Moreover, we separated and purified AChE by using a one-step column chromatography technique, which could be an alternative method. Based on the results, the appropriate glyphosate concentration for induction of AChE in juvenile catfish hybrids was 0.2 ml/ L while that in adult was 0.75 ml/L. And, hydroxyapatite was applied as a media for separation and 0.2 M phosphate buffer was applied for protein elution.  After comparing the suitability of hybrid catfish for extracting AChE, it was found that adult hybrid catfish was more suitable than the juvenile. The molecular weight of separated AChE was 71 kDa when studied by using SDS-PAGE and Western blot techniques. For our results, the columnar chromatography technique with hydroxyapatite was likely to be used to purify AChE from the brain of a hybrid catfish in only one step. This is a useful alternative method in separating AChE in order to apply as an antigen to detect pesticide exposure. And, it can be further applied to production of polyclonal antibodies and monoclonal antibodies specific to AChE for monitoring of pesticide exposure. Keywords: acetylcholinesterase, glyphosate, antibody techniques, toxicity testing